Limnology of Lake Bogakain, Bandarban, Bangladesh - Khondker, Moniruzzaman; Alfasane, Md Almujaddade; Islam, Md Shafiqul; Bhuiyan, M Azmal Hossain; Gani, Md Ataul (Bangladesh Journal of Botany, 2011)
Bogakain, a natural high altitude (372 m) lake of Bangladesh has been limnologically investigated for the first time. At mid-point, the depth of the lake was measured 46.54 m and the Secchi visibility was 2.37 m. Water temperature from 1-10 m depth gradient showed slight stratification in the lake which varied from 27.0 - 22.4° C at 1.00 pm. pH at the different depths ranged from 7.8 - 9.1, conductivity from 75 - 80 μS/cm and TDS from 39 - 42 mg/l. Alkalinity ranged from 0.8 - 1.24 meq/l and DO from 0.61 - 11.39 mg/l. A total of 40 species of phytoplank-ton were recorded from the lake of which 21 belonged to Chlorophyceae followed by Cynaophyceae (5), Bacillariophyceae (4), Cryptophyceae (4), Euglenophyceae (3), Dinophyceae (2) and Chrysophyceae (1). Bloom by Synnechocystis salina Wisl was observed at 10 m depth. Water temperature correlated negatively and significantly with depth. Phytoplankton biomass as chl a correlated positively with phytoplankton density and water depth. The former variable showed negative correlation with pH and water temperature. Lake Bogakain is the deepest natural lake of Bangladesh and many of the previous concepts regarding the lake i.e., fishless, highly turbid water and it has got a thermal spring at the bottom was found invalid. Key words: Bogakain; Limnology; Macrophyte; Phytoplankton; Bangladesh DOI: 10.3329/bjb.v39i2.7301 Bangladesh J. Bot. 39(2): 153-159, 2010 (December)